High content analysis of primary macrophages hosting proliferating Leishmania amastigotes: application to anti-leishmanial drug discovery. - Nathalie Aulner; Anne Danckaert; Eline Rouault-Hardoin; Julie Desrivot; Olivier Helynck; Pierre-Henri Commere; Hélène Munier-Lehmann; Gerald F Späth; Spencer L Shorte; Geneviève Milon; Eric Prina (PLoS Neglected Tropical Diseases)
Background/objectives Human leishmaniases are parasitic diseases causing severe morbidity and mortality. No vaccine is available and numerous factors limit the use of current therapies. There is thus an urgent need for innovative initiatives to identify new chemotypes displaying selective activity against intracellular Leishmania amastigotes that develop and proliferate inside macrophages, thereby causing the pathology of leishmaniasis. Methodology/principal findings We have developed a biologically sound High Content Analysis assay, based on the use of homogeneous populations of primary mouse macrophages hosting Leishmania amazonensis amastigotes. In contrast to classical promastigote-based screens, our assay more closely mimics the environment where intracellular amastigotes are growing within acidic parasitophorous vacuoles of their host cells. This multi-parametric assay provides quantitative data that accurately monitors the parasitic load of amastigotes-hosting macrophage cultures for the discovery of leishmanicidal compounds, but also their potential toxic effect on host macrophages. We validated our approach by using a small set of compounds of leishmanicidal drugs and recently published chemical entities. Based on their intramacrophagic leishmanicidal activity and their toxicity against host cells, compounds were classified as irrelevant or relevant for entering the next step in the drug discovery pipeline. Conclusions/significance Our assay represents a new screening platform that overcomes several limitations in anti-leishmanial drug discovery. First, the ability to detect toxicity on primary macrophages allows for discovery of compounds able to cross the membranes of macrophage, vacuole and amastigote, thereby accelerating the hit to lead development process for compounds selectively targeting intracellular parasites. Second, our assay allows discovery of anti-leishmanials that interfere with biological functions of the macrophage required for parasite development and growth, such as organelle trafficking/acidification or production of microbicidal effectors. These data thus validate a novel phenotypic screening assay using virulent Leishmania amastigotes growing inside primary macrophage to identify new chemical entities with bona fide drug potential.